Are thermal constants constant? A test using two species of ladybird - Jarošík, V; Kumar, G; Omkar; Dixon, A F G (Journal of thermal biology, 2014)
There is a controversy about whether the thermal constants, lower developmental threshold, rate of development and corresponding degree days required for development, change when a species is reared under different developmental conditions. We present a more precise way of measuring these constants using the linear relationship between the rate of development and temperature. First we use the equation proposed by Ikemoto and Takai (2000) to determine the linear phase of development and then a generalised linear model having a different variance at low and high temperatures, specific for each condition, to estimate the parameters of the linear relationship. Using this method, we show that providing the difference in food quality is sufficiently great, an aphidophagous ladybird develops significantly faster and starts developing at a significantly lower temperature on a good than on a poor quality diet. Adaptive significance of the thermal constants not remaining constant is discussed in terms of a trade-off between growth and rate of development, when temperature and food quality varies.
Keywords: Food quality; Animals; Hot Temperature; dieta; brouci; Menochilus sexmaxculatus; zvířata; Hemiptera; Diet; Linear phase of development; Propylea dissecta; Coleoptera; vysoká teplota; Degree days; Lower developmental threshold